Basic Unit Layer Rate Control Algorithm for H.264 Based on Human Visual System. (12th November 2013) - Chen, Xiao; Liu, Haiying
Abstract : In the process of the video coding, special attention should be paid to the subjective quality of the image. In the JVT-G012 algorithm for H.264, the influence of the human visual characteristic in basic unit layer rate control was not taken into account. This paper takes the influence of the human visual characteristic into the full consideration and offers ways to improve the subjective quality of the image. The visual characteristic factor, which is constituted by the motion feature and edge feature, is used to reasonably allocate the target bits, and then its quantization parameter is adjusted by encoded frame information. The experimental results show that, in comparison to the original algorithm, the proposed algorithm can not only control the bit rate more accurately but also make the peak signal to noise ratio (PSNR) stable, so as to improve the stationarity of the video image. The subjective quality of the reconstructed video is more satisfying.